Qualidade de vida, autoeficácia e autoestima de gestantes de baixo risco - Mazziero, Patricia Fernanda Evaristo (2024)
Pregnancy is a period of intense changes for women, both in their body and in their lives, involving significant physical and hormonal changes. Even in low-risk pregnancies, changes are observed that can impact the quality of life of pregnant women and affect their health and that of the newborn. The way pregnant women experience these changes has repercussions on the formation of their maternity and on their relationship with their child. The self-esteem of the pregnant woman is pointed out in the literature as one of the important factors for bonding with the child, self-efficacy can favor the development of skills and contribute to coping with the alterations. Objective: To evaluate the quality of life of low-risk pregnant women and associations with self-efficacy and self-esteem. Method: This is a descriptive, cross-sectional study with a quantitative approach. It was developed in the city of Mococa-SP, in the primary care services of the municipal health network. The sample consisted of 135 pregnant women at different gestational stages. Pregnant women over 18 years of age and involved in active prenatal care were included. The study was approved by the Human Research Ethics Committee of UFSCar. All ethical principles established in CONEP Resolution No. 510 of April 7, 2016 were followed. The collection period was from July to October 2023. Results: Pregnant women had high levels of general quality of life and satisfaction with health, high levels of self-efficacy and unsatisfactory self-esteem occurred in a high percentage (81%). There was an association with quality of life and self-efficacy (p<0.005) and with sociodemographic and clinical data (p<0.05) in the physical, social relationship and environment domains. There was no association between self-esteem and self-efficacy (p=0.40). Conclusion: Pregnant women in general had adequate levels of quality of life and were satisfied with their health. They also had high self-efficacy, but decreased self-esteem. There are sociodemographic and clinical factors such as being black, having previous abortions, previous vaginal births, previous pregnancies, and having several people living in the house that were associated with certain domains for worse quality of life. The present study may contribute to clinical practice, since it points to the possibility of care focused on the specific needs of this population that go beyond the physical scope. It is suggested that new studies on quality of life, self-efficacy and self-esteem in pregnant women should be carried out, given the scarcity of studies that investigated these variables together and given the relevance of a greater understanding of the factors that influence them, which may favor the production of more robust data and contribute to the quality of care for pregnant women.